Raman spectroscopy of two-dimensional material under high pressure: Black phosphorus ultrathin film, phosphorene. (13th April 2017) - Sasaki, Taizo; Kondo, Kensuke; Akahama, Yuichi; Nakano, Satoshi; Taniguchi, Takashi
Abstract: Raman spectroscopy of phosphorene has been carried out at room temperature as a function of applied pressure. At ambient pressure, frequency of the and modes for the monolayer (1L) and bilayer (2L) showed different values from the bulk sample. The difference in frequency was observed both for diamond and hexagonal-BN substrates and was enhanced under high pressure. The 1L and 2L structures are stable up to around 15 and 11 GPa, respectively, while the trilayer (3L) phosphorene is transformed into the As-type (A7) structure at 4.5 GPa so as the bulk material For 2L phosphorene, the Eg and A1g modes of the A7 phase newly appeared in the low-frequency side of the mode while for 1L phosphorene a broad band was observed at 280 cm −1 above 15 GPa corresponding to a structural phase transition. Since the observed pressure effects do not depend on the substrate and the pressure medium, they are intrinsic to phosphorene. Theoretical analyses have been performed for the pressure dependence of the Ag modes by incorporating model geometry to simulate the two-dimensional system in the pressure medium.